Basics of Stem Cells and Preclinical Testing - Rao, K. Suryanarayana (Biology, Engineering, Medicine and Science Reports)
Stem cells are undifferentiated biological cells that can differentiate into specialized cells and can divide to produce more stem cells. They are found in multicellular organisms. In mammals, there are two broad types of stem cells: embryonic stem cells, which are isolated from the inner cell mass of blastocysts, and adult stem cells, which are found in various tissues. In adult organisms, stem cells and progenitor cells act as a repair system for the body, replenishing adult tissues. In a developing embryo, stem cells can differentiate into all the specialized cells—ectoderm, endoderm and mesoderm—but also maintain the normal turnover of regenerative organs, such as blood, skin, or intestinal tissues.